Using Synchrotron Radiation Imaging Techniques to Elucidate the Actions of Hexarelin in the Heart of Small Animal Models - Waddingham, Mark T.; Tsuchimochi, Hirotsugu; Sonobe, Takashi; Asano, Ryotaro; Jin, Huiling; Ow, Connie P. C.; Schwenke, Daryl O.; Katare, Rajesh; Aoyama, Kohki; Umetani, Keiji; Hoshino, Masato; Uesugi, Kentaro; et al. (Frontiers in Physiology, 2022)
The majority of the conventional techniques that are utilized for investigating the pathogenesis of cardiovascular disease in preclinical animal models do not permit microlevel assessment of in situ cardiomyocyte and microvascular functions. Therefore, it has been difficult to establish whether cardiac dysfunction in complex multiorgan disease states, such as heart failure with preserved ejection fraction and pulmonary hypertension, have their origins in microvascular dysfunction or rather in the cardiomyocyte. Herein, we describe our approach of utilizing synchrotron radiation microangiography to, first, ascertain whether the growth hormone secretagogue (GHS) hexarelin is a vasodilator in the coronary circulation of normal and anesthetized Sprague-Dawley rats, and next investigate if hexarelin is able to prevent the pathogenesis of right ventricle (RV) dysfunction in pulmonary hypertension in the sugen chronic hypoxia model rat. We show that acute hexarelin administration evokes coronary microvascular dilation through GHS-receptor 1a and nitric oxide, and through endothelium-derived hyperpolarization. Previous work indicated that chronic exogenous administration of ghrelin largely prevented the pathogenesis of pulmonary hypertension in chronic hypoxia and in monocrotaline models. Unexpectedly, chronic hexarelin administration prior to sugen chronic hypoxia did not prevent RV hypertrophy or RV cardiomyocyte relaxation impairment. Small-angle X-ray scattering revealed that super relaxed myosin filaments contributed to diastolic dysfunction, and that length-dependent activation might contribute to sustained contractility of the RV. Thus, synchrotron-based imaging approaches can reveal novel insights into cardiac and coronary functions in vivo.